SISTEM PENDUKUNG KEPUTUSAN UNTUK PENENTUAN BARANG KONVEKSI YANG HARUS DISEDIAKAN MENGGUNAKAN METODE PROMETHEE - , IRWANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Decision support system is a tool used by decision makers for making decision with variety methods. Problems that occurred is how to determine the most demanded items by customers . Decision support systems is necessary to raise the computing speed in decision-making alternatives. A decision support system should be made, so the director / head of the company can make decisions based on criteria that have been set. This decision support system uses promethee method which use some type and maximum-minimum rules. Result of promethee method is item ranking. To determine the rating of a rank, this research used leaving flow, entering flow and net flow, as well as the type of preferences that have been defined. The result of this study are 75 names of convection items and 57 respondents indicated that Japan's lime is the top ranked item by the value of 0.819. The data is retrieved based on discount, quality, brand, the ease of obtaining items, satisfaction, prices, and employee services. Keywords: Decision support systems, Promethee, Leaving flow, Entering flow, Net flow